Kemampuan Numerasi di Sekolah Dasar: Systematic Literature review - Nadiatussalma, Nadiatussalma; Surya, Anesa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Numeracy is an important skill for learners to master in understanding and solving daily life problems. This study aims to comprehensively review the literature on numeracy skills of primary school students. This research method is a systematic literature review (SLR). The scientific articles analyzed were articles published from 2020 - 2025 using the keywords numeracy skills, student numeracy factors, mathematical reasoning, and elementary school in the Google Scholar database. The results showed that the numeracy skills of primary school students are basic skills that are broader than ordinary mathematical calculations, including the application of numbers and mathematical symbols to solve various issues faced in everyday life, as well as the ability to analyze data in various formats. Various factors affect numeracy skills, namely cognitive and non-cognitive aspects (self-confidence, mathematical disposition, discipline), variations in student ability levels, lack of numeracy literacy-related training, as well as learning approaches and curricula that need to be adapted to the context of students' real lives.  Thus, it is necessary to improve efforts in developing primary school students' numeracy skills through innovative learning strategies by considering other factors that influence it.Kemampuan numerasi merupakan kemampuan yang penting untuk dikuasai peserta didik dalam memahami dan memecahkan masalah kehidupan sehari-hari. Penelitian ini bertujuan untuk mengkaji literatur tentang kemampuan numerasi siswa sekolah dasar dengan secara komprehensif. Metode penelitian ini adalah systematic literature review (SLR). Artikel ilmiah yang dianalisis merupakan artikel yang diterbitkan dari tahun 2020 – 2025 dengan menggunakan kata kunci kemampuan numerasi, faktor numerasi siswa, penalaran matematis, dan sekolah dasar pada database Google Scholar. Hasil penelitian menunjukkan bahwa kemampuam numerasi siswa sekolah dasar merupakan keterampilan dasar yang lebih luas dari perhitungan matematika biasa, meliputi penerapan angka serta simbol matematika untuk memecahkan berbagai isu yang dihadapi dalam keseharian, serta kemampuan dalam menganalisis data dalam beragam format. Berbagai faktor yang berpengaruh terhadap kemampuan numerasi yaitu aspek kognitif dan non-kognitif (self eficacy, disposisi matematis, kedisiplinan), variasi dalam tingkat kemampuan siswa, minimnya latihan terkait literasi numerasi, serta pendekatan pembelajaran dan kurikulum yang perlu disesuaikan dengan konteks kehidupan nyata siswa.  Dengan demikian diperlukan upaya peningkatan dalam mengembangkan kemampuan numerasi siswa sekolah dasar melalui strategi pembelajaran yang inovatif dengan mempertimbangkan faktor-faktor lain yang memengaruhinya.